Statins Reduce Melanoma Development and Metastasis through MICA Overexpression - Pich, Christine; Teiti, Iotefa; Rochaix, Philippe; Mariamé, Bernard; Couderc, Bettina; Favre, Gilles; Tilkin-Mariamé, Anne-Françoise (Frontiers in Immunology, 2013)
Survival of melanoma patients after metastases detection remains short. Several clinical trials have shown moderate efficiency in improving patient survival, and the search for pharmacological agents to enhance the immune response and reduce melanoma metastases is still necessary. Statins block the mevalonate pathway, which leads to decreases in GTPase isoprenylation and activity, particularly those of the Ras superfamily. They are widely used as hypocholesterolemic agents in cardiovascular diseases and several studies have shown that they also have protective effects against cancers. Furthermore, we have previously demonstrated that treatment of melanoma cells with inhibitors of the mevalonate pathway, such as statins, favor the development of specific adaptive immune responses against these tumors. In the present study, we tested statin impact on the innate immune response against human metastatic melanoma cells. Our data shows that treatment of two human melanoma cell lines with statins induced a weak but significant increase of MICA membrane expression. PPARγ is involved in this statin-induced MICA overexpression, which is independent of Ras and Rho GTPase signaling pathways. Interestingly, this MICA overexpression makes melanoma cells more sensitive to in vitro lysis by NK cells. The impact of statin-treatment on in vivo development of melanoma tumors and metastases was investigated in nude mice, because murine NK cells, which express NKG2D receptors, are able to recognize and kill human tumor cells expressing MICA. The results demonstrated that both local tumor growth and pulmonary metastases were strongly inhibited in nude mice injected with statin-treated melanoma cells. These results suggest that statins could be effective in melanoma immunotherapy treatments.